Maternal and fetal factors affecting cord plasma leptin and adiponectin levels and their ratio in preterm and term newborns: New insight on fetal origins of metabolic dysfunction. Issue 2 (18th November 2022) - Makker, Kartikeya; Zhang, Mingyu; Wang, Guoying; Hong, Xiumei; Aziz, Khyzer B.; Wang, Xiaobin
Abstract : Background: Understanding of maternal and fetal factors affecting leptin, adiponectin, and adiponectin:leptin ratio at birth may provide valuable insights into potential future risk of metabolic alterations and inform primordial prevention and precision nutrition strategies. The objective of this study is to identify maternal and fetal risk factors that affect leptin and adiponectin levels (markers of adiposity) and adiponectin/leptin ratio (a marker of dysfunctional adipose tissue) at birth. Methods: We studied mother–infant pairs in the Boston Birth Cohort. Cord blood was collected at birth. We used student t - tests to compare log normalized cord leptin and adiponectin levels. Regression analysis was performed to examine the association of maternal and fetal factors with leptin and adiponectin levels and adiponectin:leptin ratio at birth in both term and preterm infants. Results: We analyzed 1012 infants (245 preterm). Both cord leptin and adiponectin were higher in term infants than preterm infants (10.2 ± 0.9 vs. 9.2 ± 1.3, P < 0.0001 and 9.5 ± 0.7 vs. 8.9 ± 0.8, P < 0.0001, respectively). Cord leptin was higher for Black infants (10.1 ± 1.1 vs. 9.9 ± 1.2; P < 0.001) although Black (ref: non-Black) infants had lower cord adiponectin levels (9.3 ± 0.8 vs. 9.5 ± 0.7; P = 0.01). Ratio of adiponectin to leptin (log normalized) was higher in preterm infants (−0.24) vs. term infants (−0.69). On regression analysis, cord leptin was positively associated with longer gestational age (GA), birth weight z score, Black race, maternal overweight and obesity, gestational diabetes and pregestational diabetes mellitus and negatively associated with male sex. Cord adiponectin was positively associated with GA, birth weight z score and negatively with Black race and male sex. Adiponectin:leptin ratio was positively with male sex and negatively with GA, birth weight z score, Black race, gestational DM, pregestational DM and maternal overweight and obesity. Conclusions: We identified several factors that affect leptin and adiponectin levels along with adiponectin–leptin ratio at birth beyond GA and birth weight which could also play an important role in influencing the trajectory of these hormones and future cardiometabolic outcomes. This knowledge can help tailor precision nutrition interventions.